2001
DOI: 10.1090/s0002-9939-01-06253-0
|View full text |Cite
|
Sign up to set email alerts
|

A family of quadratic polynomial differential systems with invariant algebraic curves of arbitrarily high degree without rational first integrals

Abstract: Abstract. We give a class of quadratic systems without rational first integral which contains irreducible algebraic solutions of arbitrarily high degree. The construction gives a negative answer to a conjecture of Lins Neto and others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…In that work all the invariant algebraic curves linear in the variable y, that is, defined by f (x, y) = p 1 (x)y + p 2 (x), where p 1 and p 2 are polynomials, are determined. The example appearing in [8] is a further study of an example appearing in [7] and the example given in [11] is also described in [7]. We show that all these quadratic systems, with an invariant algebraic curve of arbitrary degree can be constructed by the method explained in the previous section.…”
Section: Lemma 13mentioning
confidence: 85%
See 4 more Smart Citations
“…In that work all the invariant algebraic curves linear in the variable y, that is, defined by f (x, y) = p 1 (x)y + p 2 (x), where p 1 and p 2 are polynomials, are determined. The example appearing in [8] is a further study of an example appearing in [7] and the example given in [11] is also described in [7]. We show that all these quadratic systems, with an invariant algebraic curve of arbitrary degree can be constructed by the method explained in the previous section.…”
Section: Lemma 13mentioning
confidence: 85%
“…In [7] it is shown that, in case n ∈ N, an irreducible polynomial of degree n belonging to a family of orthogonal polynomials is a solution of equation (11). For instance, when Ω 1 (x) = 1, we get the Hermite polynomials, when Ω 1 (x) = x, we get the Generalized Laguerre polynomials and when Ω 1 (x) = 1 − x 2 , we get the Jacobi polynomials.…”
Section: Lemma 13mentioning
confidence: 99%
See 3 more Smart Citations